GAYA HIDUP HEDONISME MAHASISWI UNIVERSITAS RIAU DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Cici Febrianti; Swistantoro " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Kelurahan Simpang Baru Kecamatan Tampan Kota Pekanbaru.The purpose of this study was to determine the forms of hedonism student lifestyle in Kelurahan Simpang Baru KecamatanTampan Kota Pekanbaru. This study titled “Lifestyle Hedonism Student in Kelurahan Simpang Baru KecamatanTampan Kota Pekanbaru”. Topics focus of this research is how the hedonistic lifestyle impacts students in Kelurahan Simpang Baru. Object Research is a student at the University of Riau domiciled in Kelurahan Simpang Baru. The sample in this study amounted to 10 people. The author uses descriptive quantitative method and the data were analyzed qualitatif and using retrieval techniques Puspoive sampling. Instruments of data are observation, questionnaires and documentation. From research conducted, the authors found that the consumption patterns coed Universitas Riau in Kelurahan Simpang Baru characterized by a pattern kosumsi such as: Needs Student In Entertainment, The World Tonight Will student needs,like to buy expensive things.Universitas Riau student hedonistic lifestyle has some positive and negative effects. The positive impact is composed of: foster self-confidence, expanding the scope of friendship. The negative impact of a hedonistic lifestyle Univeritas Riau student is: never satisfied, accustomed to living lavishly, fall behind in academic, lost their identity. The sophistication of technology, communication tools, and her fashionable outfit today has claimed the attention of young people should focus on preparing themselves for the future challenges that require thought and behavior are very rational. Keywords: Lifestyle, Students Consumption Pattern